An Understanding of the Accumulation of Biomass and Nitrogen is Benefit for Chinese Maize Production. (1st March 2016) - Yan, Peng; Yue, Shanchao; Meng, Qingfeng; Pan, Junxiao; Ye, Youliang; Chen, Xinping; Cui, Zhenling
Abstract : Increasing maize ( Zea mays L.) yields depends on understanding the dynamics of biomass and N accumulation such that N demand and N supply can be synchronized and N management improved. Biomass and N accumulation data were collected at the six‐leaf (V6) stage, the flowering (VT) stage, and harvest from nine field experiments at eight sites in four key summer maize domains on the North China Plain. The data were used to investigate how grain yield and the N uptake requirement per Mg grain yield (Nreq) were related to differences in N management. Grain yield averaged 9.0 Mg ha −1 and ranged from 1.9 to 16.3 Mg ha −1 ; the highest grain yield (9.6 Mg ha −1 ) was achieved with optimal N rates (N = OPT). In N = OPT plots, increases in grain yield from <8 to 8–10 Mg ha −1 were associated with increased biomass and N accumulation beginning at stage V6; increases in grain yield from 8–10 to >10 Mg ha −1 were associated with substantial increases in biomass and N accumulation during grain filling. In N = OPT plots with >10 Mg ha −1 yield, plants had a high stover N content and maintained a high green leaf area index and SPAD, which contributed to a high harvest index, high kernel number per plant, and high thousand kernel weight. Our results indicate that farmers on the North China Plain should apply less total N fertilizer and should apply a substantial proportion of the N fertilizer after stage V6.